PENERAPAN MANAJEMEN NYERI GOUT ARTHRITIS MENGGUNAKAN CARA RENDAM KAKI AIR HANGAT DENGAN JAHE PADA KELUARGA Ny S DI KELURAHAN METESEH SEMARANG - Pujinjngsih, Kartika Dewi; Hani, Umi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Gout Arthritis otherwise known as goutis a disease and a potential disabilitydue to arthritis that has been known for a long time,Symptoms usually consist of severe episodic paininflammation of a joint. Joint inflammation in arthritisGout can occur in all joints of the bodycauses swelling, joints feel hot as wellpainful. Management of gout can be done withtwo ways namely pharmacologically and non-pharmacologicallypharmacological. Non-pharmacological treatment is carried outby soaking feet in warm water with ginger. Gingerused to treat colds, coughs, diarrhea andinflammatory joint disease such as arthritis. This case studyprovide an overview of the implementation of pain managementGout Arthritis using a warm water foot soakwith ginger with a family approach. Study resultscases after being given education and therapyhydrotherapy for 3 times a week withwithin 15-10 minutes there was a decrease in pain from 6be 4.